Pengaruhedukasi Hipertensi Dengan Media Booklet Terhadap Perilaku Self Management Pada Pasien Hipertensi Di Wilayah Puskesmas Balowerti Kediri - Wahyuni, Sri (Jurnal Ilmu Kesehatan, 2016)
Background : Hypertension is a disease which can damage the organ progressively and settled, disease caused diseases such as stroke, cardiovascular disorders, kidney failure, and other serious diseases that threaten a person's life. Self management can be applied to patients with hypertension in an effort to enhancing the knowledge, attitudes and behavior. Objective : This research aims to the influence of education booklets media to self management in patients hypertension in the Puskesmas Balowerti Kota Kediri. Methods : This type of research is quantitative, with pre-post test design in one group (one-group pre-post test design). The sample in this study were 30 respondents selected by accidental sampling. Results: based on the obtained  paired T test p-value is 0.000 <α = 0.05. Conclusions and recommendations :There is a significant effect of hypertension with the media giving education booklet on self management behaviors in patients with hypertension in the PuskesmasBalowerti Kediri. To improve the behavior of self-management in hypertensive patients can consider the provision of structured edukas use media interest, so that more effective education.